Consent for functional endoscopic sinus surgery: are we complying with the law?. Issue 1 (21st April 2022) - Raja, H; Talwar, R
Abstract: Objective: To assess the current standard of consent for functional endoscopic sinus surgery and determine whether it complies with the law following the Montgomery ruling. Methods: Ten complications following functional endoscopic sinus surgery were identified as common or serious from a literature search. Using questionnaires, ENT surgeons were asked which of these complications they discussed with patients, and patients were asked how seriously they regarded those risks using a five-point Likert scale. Results: Consent practice from 21 ENT surgeons and data from 103 patients were analysed. The 'reasonable patient' would expect to be consented for all risks, except for pain, and scarring or adhesions. Most ENT surgeons would routinely discuss all risks that were considered significant, except for facial paraesthesia (29 per cent) and damage to the nasolacrimal duct (24 per cent). A negative change in sense of smell was not mentioned by 29 per cent of surgeons. Conclusion: This paper demonstrates that the current consent process for functional endoscopic sinus surgery is likely to be substandard medicolegally.